Recombination and regeneration dynamics in FeNHC(ii)-sensitized solar cells. Issue 4 (12th December 2019) - Marchini, Edoardo; Darari, Mohamed; Lazzarin, Luca; Boaretto, Rita; Argazzi, Roberto; Bignozzi, Carlo Alberto; Gros, Philippe C.; Caramori, Stefano
Abstract : The first Fe(ii )-based sensitizer to give 1% efficiency in a DSSC. Abstract : Recombination and regeneration dynamics in Fe-NHC-sensitized DSSCs revealed incomplete injection and the detrimental effect of photoinjected electron recapture by the I3 -form of the redox electrolyte on performance. Importantly, the use of additives in the electrolyte allowed the best efficiency ever recorded for an iron-based DSSC to be reached.